Dynamique interactionnelle et négociation des ethos politique et journalistique en contexte de scandale politique. - Guylaine Martel (Communication)
The notion of “celebrity politics” encompasses a set of political representations that are not part of the traditionally accepted playbook for exercising power. Celebrity politics are defined by two main issues: interference between the political and pop culture spheres and the significant media exposure that now accrues to—and sometimes afflicts—politicians. To explore the downside of celebrity status, the author uses the case of Nathalie Normandeau, a member of the National Assembly who between 1998 and 2011 became a minister, then deputy premier of Québec under the Liberal government and who was implicated in an illegal political fundraising scheme.